Distribution of epifauna in offshore benthic environments along the west and south coast of South Africa - Shah, Aliya (Department of Biological Sciences, 2019)
Marine unconsolidated sediments, such as sand, gravel and muds, constitute the most extensive benthic ecosystems globally. Biological data for these ecosystems are frequently sparse which can hinder the success and implementation of marine management strategies for benthic ecosystems. There are limited studies in South Africa on benthic epifauna. This study investigates the composition and distribution of epibenthic invertebrate assemblages along the west and south coast of South Africa (sampled using depth-stratified demersal trawls) to inform marine environmental management. Sample depth varied from 36m to 899m. Multivariate tools (PRIMER and PERMANOVA+) were used to analyse spatial (west vs south coast) and temporal (2011 vs 2017) patterns in epifauna. This study also investigated an overlap region between the west and south coast. A group average linkage cluster analysis defined biotopes using significant branching (p< 0.05). Biotopes were compared against the 2012 National Biodiversity Assessment (NBA) benthic habitat map to investigate whether epifaunal biotopes identified, align with the existing classification. A significant difference among epifauna between region and depth was found, where the west coast had a higher average number of individuals and species per station. Sympagarus dimorphus and Pelagia noctiluca were characteristic species for west and south coast respectively. Epifauna was found to be significantly different between 2011 and 2017, with a notable increase in the abundance of Crossaster penicillatus in 2017. The majority of the biotopes aligned with the current NBA classification, in particular the Agulhas Sandy Shelf Edge ecosystem type on the south coast and South Atlantic Upper Bathyal and Namaqua Muddy Inner Shelf ecosystem types on the west coast. This thesis contributes to the mapping and description of offshore ecosystem types to inform marine environmental impact assessments, marine spatial planning and marine protected area expansion.